Mercury Hollows as Remnants of Original Bedrock Materials and Devolatilization Processes: A Spectral Clustering and Geomorphological Analysis. Issue 9 (17th September 2018) - Lucchetti, A.; Pajola, M.; Galluzzi, V.; Giacomini, L.; Carli, C.; Cremonese, G.; Marzo, G. A.; Ferrari, S.; Massironi, M.; Palumbo, P.
Abstract: We perform a detailed geomorphological and compositional analysis on three craters hosting hollows located in the Victoria and Kuiper Quadrangles of Mercury. Based on Mercury Dual Imaging System data, high‐resolution detailed geomorphological mapping is provided in order to fully characterize the geological framework where hollows formed. In addition, we apply an unsupervised spectral clustering, based on a K‐mean algorithm, to separate in clusters our data sets. The comparison between the spectral and the well‐defined geomorphological units reveals a spatially coherent distribution. In particular, all hollows are uniquely identified by a well‐defined spectrum showing a wide absorption band between 0.558 and 0.828, with a possible hint of absorption toward 1 μm. Our analysis suggests that the composition of hollows may be characterized by a mixture of different minerals contributing to the absorptions found in our spectra. Indeed, sulfides alone (CaS, MnS, and MgS) cannot explain the spectrum behavior of hollows, even if the mechanism forming hollows likely involves the loss of volatiles from the surface. Hence, we have to consider bedrock‐forming material as partial responsible of the absorptions. For the studied hollows we suggest that the bedrock‐forming minerals are pyroxenes presenting transitional elements, like Cr, Ti, and Ni in substitution of Mg and/or Fe. Therefore, we suggest that the spectral characteristics of hollows are related to both remnant material produced by devolatilization process and to bedrock in which the hollows formed. Plain Language Summary: The Mercury Surface, Space ENvironment, GEochemistry, and Ranging mission provided the first detailed view of Mercury's surface and its space environment. Among the many discoveries, it revealed for the first time the presence of unusual bright irregular and rimless flat‐floored depression, called hollows, which are usually found on crater walls, rims, floors, and central peaks. Understanding the nature of hollows is still a major challenge since it is difficult to define which is their source mechanism. By using multicolor images acquired through the Mercury Dual Imaging System, we analyzed the nature of hollows hosted by three different impact craters, both from a geomorphological and a compositional perspective. Such analysis revealed that different units identified in high‐resolution geological maps are characterized by different spectral behaviors. Hollows in all craters have a well‐defined visible spectrum that when compared with laboratory spectra is indicative of the presence of both sulfides and pyroxene presenting transitional elements. This provides new insights into the hollows' nature and composition, suggesting that hollow terrains are the expression of both the remnant material coming from a process that involve devolatilization and the bedrock‐forming material (planet crust) where they formed. Key Points: Spectral behavior of hollows is identified by a wide absorption band between 0.558 and 0.828 μm, with a hint of absorption toward 1 μm The hollow absorption can be explained by pyroxenes presenting transitional elements, in addition to sulfides Hollows consist of both the remnant material coming from a degassing process and the bedrock‐forming material in which they formed